Alternative communication for students with Autism in regular schools - Cátia Crivelenti de Figueiredo Walter; Leila Regina d'Oliveira de Paula Nunes (Universidade Federal de Santa Maria (UFSM), 2013)
The paper describes a stage of a research project about Alternative Communication for students with autism in metropolitan schools classrooms in Rio de Janeiro. The purposes of the study were both to report and to discuss the needs and desires of elementary school teachers who work in the resource rooms offering specialized educational service and participating of the inclusion process of students with autism. Teachers attended to a theoretical-practicum course about the use of adapted PECS, an Alternative Communication system that functions by the exchange of pictures, and is specially tailored for students with autism. By the end of the course, the participants were asked about their needs and desires related to the employment of this resource in the regular classroom. The results showed that the majority of the teachers presents intention for better communication with their students , expressing, nonetheless, the need for both support from specialized teachers and the active participation of all people involved with the inclusion process. The participants considered that Alternative Communication should be introduced first in the resource rooms and later on in the regular classroom, as well.